Criminal liability for non-compliance of industrial court's award - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (LexisNexis, 2015)
The Industrial Court would, as a general rule, in a complaint of non-compliance, look at the terms of the award by confining itself within the four walls of the award and determine whether the terms of the award had been complied with. Where the court is satisfied that there has been non-compliance by the employer, and where the employer has no special circumstances warranting the variation or setting aside of the award under s 56(2) of the Industrial Relations Act 1967 ('the IRA'), the court will make an order that the employer has to comply with the said award within the period stipulated, from the date of service of the court's orderfor compliance. Failure to comply with the order of the Industrial Court is brought in a non-compliance proceeding and is backed by criminal sanction. In relation to criminal liability, the veil ofthe company could be lifted to make the directors of the company personally liable for non-compliance of the award of the Industrial Court. However, it must be noted that the Industrial Court can only impose the criminal sanction with the written consent ofthe Public Prosecutor. The court has no inherent power of its own to punish an employer who disregards the order of the court. Hence, this paper is intended to look into the enforcement of the Industrial Court award with specific reference to the criminal liability of the employer under s 56(3) ofthe IRA. It will be submitted that the Industrial Court should be given the power to enforce its own award and to penalise the defaulter so that the benefits of the award are realised.